Patrimoine naturel et médiations visuelles : les solutions du paysage - Catherine Saouter (VertigO)
This article questions the notion of natural heritage from the perspective of one of its symbolic representations : the landscape. Since heritage and landscape are not ontological objects but rather cultural constructs, the study focuses on the semiotic and historic processes which preside over their invention and their interrelation, in order to identify the tensions and contradictions at work in the process of considering nature as heritage. Three inventions make up the prerequisites for this process : nature, a way of looking and landscape. The study presents, diachronically, the historic milestones of this process which originates, in the Western world, during the Renaissance period. From then on, the emergence of the paradigm of modernity slowly leads to an alliance, fully achieved during the 19th century, between intellectual curiosity, scientific systematization and aesthetic emotion. This alliance is key to the development of the contemporary taste for natural heritage, as it is reflected in Unesco’s agreement on the subject. However, the standpoint in favor of heritage, by overvaluing the aesthetics of the landscape, creates the illusion of preserving nature and can even hinder this very preservation. The study of landscape therefore reveals the paradox and the inner contradictions of the project to consider nature as heritage.